New naratif the first year - Han, Kristen; Thum, Ping Tjin (Pagesetters Services Pte Ltd., 2018)
New Naratif is a a movement for democracy, freedom of expression, and freedom of information in Southeast Asia (Indonesia, Timor Leste, Singapore, Malaysia, Thailand, Laos, Brunei, Cambodia, Vietnam, Myanmar and the Philippines). We achieve this through journalism, research, art, and community-building. "New Naratif: The First Year" is an anthology of our best articles from our first year (September 2017 to September 2018). Our stories, research articles, and comics cover a range of topics and issues across the region. From press freedom to LGBT equality, healthcare to the environment, we look beyond stereotypes and assumptions to explore the underlying forces that shape this region that's our home.